Pengaruh Kompentensi Auditor, Independensi Dan Tekanan Waktu (TIME PRESSURE) Terhadap Kemampuan Auditor Mendeteksi Fraud - Velisa Mita Chornaini; Dewi Saptantinah (Universitas 17 Agustus 1945 Semarang, 2024)
Now, the main topic in the media is accounting fraud, or fraud, in accounting parlance. Internal and external fraud are the two main types of fraud. However, fraud detection itself aims to determine whether fraud has occurred, who the perpetrator is, who the victim is, and how it happened. This research aims to determine how competence, lndependence, and time pressure affect the auditor's abiIity to discover fraud. In this research, initial data was obtained from auditors' answers from KAP Central Java and DIY. MuItiple Iinear regression anaIysis was used to anaIyze the data. The resuIts of data anaIysis show that there is a positive and significant coefficient on the influence of auditor competency (X1) and independence (X2) on the auditor's abiIity to detect fraud. but tlme pressure (Y) has no impact on the auditor's abiIity to discover fraud. To achieve the objectives of this research, sample criteria for position and length of service have been established, the sample size has been increased, and moderating variables have been added to future research.